1992
DOI: 10.2331/suisan.58.337
|View full text |Cite
|
Sign up to set email alerts
|

Effect of L-Ascorbyl-2-phosphate-Mg on the Yellowtail Seriola quinqueradiata as a Vitamin C Source.

Abstract: A stable form of vitamin C, L-ascorbyl-2-phosphate-Mg (APM), was tested for efficacy as a vitamin C source in the juvenile yellowtail Seriola quinqueradiata. The fish, weighing 2.67g, were fed 4 fish meal-based diets containing graded levels of supplemental APM (0, 3, 6, and 10mg/100g diet) for 83 days. The fish receiving the diet without supplemental APM showed deficiency symptoms such as reduced growth rate, deformity (lordosis and scoliosis), distorted gill support cartilage (degeneration of the ravine part… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
11
1
2

Year Published

1994
1994
2017
2017

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 32 publications
(16 citation statements)
references
References 10 publications
2
11
1
2
Order By: Relevance
“…We found that the highest level of vitamin C content in the liver and muscle tissues were in the diets supplemented with encapsulated and crystallized ascorbic acid, alone or in combination with the soybean lecithin. Similar results were obtained by Kanazawa et al (1992) on Japanese amberjack (Seriola quinqueradiata), El Naggar and Lovell (1991) and by Li et al (1998) in channel catfish (Ictalurus punctatus) and Grant et al (1989) and Matusiewicz et al (1994) on rainbow trout (Oncorhynchus mykiss). Due to the vitamin C deficiency, structural deformities such as scoliosis and lordosis have been observed in channel catfish (Wilson, 1973;Andrews and Murai, 1975;Lim and Lovell, 1978;Wilson et al, 1989).…”
Section: Discussionsupporting
confidence: 73%
“…We found that the highest level of vitamin C content in the liver and muscle tissues were in the diets supplemented with encapsulated and crystallized ascorbic acid, alone or in combination with the soybean lecithin. Similar results were obtained by Kanazawa et al (1992) on Japanese amberjack (Seriola quinqueradiata), El Naggar and Lovell (1991) and by Li et al (1998) in channel catfish (Ictalurus punctatus) and Grant et al (1989) and Matusiewicz et al (1994) on rainbow trout (Oncorhynchus mykiss). Due to the vitamin C deficiency, structural deformities such as scoliosis and lordosis have been observed in channel catfish (Wilson, 1973;Andrews and Murai, 1975;Lim and Lovell, 1978;Wilson et al, 1989).…”
Section: Discussionsupporting
confidence: 73%
“…Because AA is water soluble, L‐ascorbylpalmitate, L‐ascorbyl sulphate and L‐ascorbyl‐2 polyphosphate generally are used as vitamin C sources in fish feed, but the phosphate derivatives of AA are more effective among all the vitamin C sources (Dabrowski, ; Halver & Hardy, ; NRC, ). Most authors worked in the area of vitamin C nutrition in fish used phosphate derivatives of AA for different fish species, such as Channel catfish, Ictalurus punctatus (Wilson et al., ); Rainbow trout, Oncorhynchus mykiss (Cho & Cowey, ; Matusiewicz, Dabrowski, Volker, & Matusiewicz, ); Tilapia, Oreochromis niloticus (Shiau & Hsu, ; Soliman et al., ); Japanese yellowtail, Seriola quinqueradiata (Kanazawa, Teshima, Koshio, Higashi, & Itoh, ); Mahseer, Tor putitora (Khan et al., ); and Magur, Clarias batrachus (Narra, Rajender, Reddy, Rao, & Begum, ). Therefore, we used L‐ascorbyl‐2 polyphosphate as a AA source in the present study.…”
Section: Discussionmentioning
confidence: 99%
“…Phosphate derivatives of AA, which are more stable and bioavailable forms of AA, are currently available and shown to have antiscorbutic activity in channel catfish [5], tilapia [13], rainbow trout [14], yellowtail [15], olive flounder [16] and parrot fish [17].…”
Section: Introductionmentioning
confidence: 99%